THE ANTIBACTERIAL ACTIVITY OF CLAUSENA ANISATA HOOK, A SOUTH AFRICAN MEDICINAL PLANT - Lawal, Ibraheem Oduola; Grierson, Don S; Afolayan, Anthony AJ (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Clausena anisata Hook also known as Iperepesi in Xhosa language is a medicinal plant used traditionally for the treatment of various ailments and some opportunistic infections associated with tuberculosis (TB). Patients in South Africa based on the phytotherapeutic information on this species in the Eastern Cape, use this medicinal plant. Hence, the antibacterial activity of various solvent extracts of the leaves and barks were respectively, evaluated using selected bacterial strains. Method: The leaves and stem bark were tested against 10 selected strains of Gram - positive and Gram - negative bacteria through the agar dilution method. Acetone, dichloromethane and water extracts were used for the extraction. MIC was determined at different concentrations (0.1mg/ml, 0.5mg/ml, 1mg/ml and 5mg/ml) and the results obtained were compared to that of standard antibiotics. Result: The acetone extract of the leaves were more active against both Gram-positive and Gram –negative bacteria with MIC ranging from 0.1 mg/ml - 0.5 mg / ml. The dichloromethane extract of the bark showed appreciable activities against Staphylococcus aureus (ATCC 6538) (MIC: 0.1mg /ml) Escherichia coli and, Streptococcus pyogenes with an MIC of 5mg/ml respectively. On the other hand, the aqueous extract of the leaves showed no activity against the tested organisms with the exception of the aqueous bark extract which inhibited Staphylococcus aureus (MIC: 0.5mg/ml) and Pseudomonas aeruginosa (MIC: 5mg/ml). Conclusion: This study confirmed the antibacterial activities of acetone extract of the leaves of Clausena anisata. The capability of this extract to inhibit both Gram positive and negative bacteria is an indication that the extract is a potential broad spectrum antibacterial. The result of this study further justified its indigenous use for the treatment of bacteria commonly associated with TB especially among the people of Nkonkobe Municipality.